Community and public health posting MDP 40110 : a cross-sectional study on knowledge, attitude and practice towards diabetes mellitus and the distribution of diabetes mellitus among the population aged 35 years and above from 15 June to 30 July 2002 at Kampung Babu, Debak - Tiong, Ing Khieng; Lee, Melina Lai Ching; Tye, Mei Hoong; Chin, Im Im; Dainna A., Gimbalu Kampun; Azizah, Saie; Safrina, Bt. Othman; Zainil Ekram, B. Abd. Wahap; Ayu Akida, Abdul Rashid; Haslan, B. Ottot; Liu, Yu Chun (Universiti Malaysia Sarawak, (UNIMAS), 2002)
A cross sectional study on knowledge, attitude, and practice toward diabetes mellitus and the distribution of diabetes mellitus among the population aged 35 and above was carried out at Kampung Babu, Debak, from 15 June to 30 July 2002 by fourth year medical students from the Faculty of Medicine and Health Science, University Malaysia Sarawak (UNIMAS). 158 respondents who are chosen through universal sampling were interviewed face-to-face from door to door using semi-structured questionnaires. The data collected was analyzed by using SPSS for windows. About two third (65.2%) of the respondents were female due to the fact that most of the males work outstation. It was also found that half of respondents (52%) had not received any formal education. Screening clinic session on 138 respondents found that there were 10 diabetic patients, which gave the prevalence of diabetes mellitus among adult population aged 35 and above, 7.2%. Out of total 10 cases, 4 were known cases, 6 were newly diagnosed cases. Three quarters (75%) of the respondents heard about diabetes mellitus. Half of them claimed that they heard about diabetes mellitus through their family member, friends, and neighbors. It was found that the respondents had low knowledge level with regards to all aspects of knowledge about diabetes mellitus with the highest was knowledge about complication (35%) and the lowest was knowledge about treatment (17%). The major reason that level of knowledge about diabetes was inadequate was that half of the respondents had not received any formal education. Test showed that there was a significant relationship on knowledge about diabetes mellitus to educational level. It was a good sign that 57% of the respondents had positive attitude toward treatment and prevention of diabetes mellitus. The majority of the respondents choose to seek medical attention if they were told to have diabetes mellitus. There was significant impact on attitude toward treatment and prevention of diabetes mellitus as age decrease and educational level increase (p<0.05). 60% of the respondents engaged in positive practice on preventive measures of diabetes mellitus. Such practice appeared to be more influence by their traditional lifestyle and religion especially regarding the methods of cooking, sugar intake, and alcohol consumption. However, most of the respondents had inadequate exercise practice in terms of duration and frequency of exercise weekly. It is believe that knowledge, attitude and practice can determine the health status of the community. By having a sufficient knowledge about diabetes can facilitate and motivate the community to improve their heath status. This subsequently changes the attitude and practice of the community regarding diabetes mellitus. After the survey, an intervention program with the theme "Kenali Kencing Manis - Hidup Sihat" was carried out at the study area on the 19 July 2002. This program was aimed to improve and to bring about a positive change in the knowledge, attitude and practice toward diabetes mellitus among the population studied.